Extracorporeal membrane oxygenation versus conventional rewarming for severe hypothermia in an urban emergency department. (6th September 2022) - Prekker, Matthew E.; Rischall, Megan; Carlson, Michelle; Driver, Brian E.; Touroutoutoudis, Melissa; Boland, Jessica; Hu, Michael; Heather, Beth; Simpson, Nicholas S.
Abstract: Background: Severe hypothermia (core body temperature < 28°C) is life‐threatening and predisposes to cardiac arrest. The comparative effectiveness of different active internal rewarming methods in an urban U.S. population is unknown. We aim to compare outcomes between hypothermic emergency department (ED) patients rewarmed conventionally using an intravascular rewarming catheter or warm fluid lavage versus those rewarmed using extracorporeal membrane oxygenation (ECMO). Methods: We performed a retrospective cohort analysis of adults with severe hypothermia due to outdoor exposure presenting to an urban ED in Minnesota, 2007–2021. The primary outcome was hospital survival. We also calculated the rewarming rate in the 4 h after ED arrival and compared these data between patients rewarmed with ECMO (the extracorporeal rewarming group) versus without ECMO (the conventional rewarming group). We repeated these analyses in the subgroup of patients with cardiac arrest. Results: We analyzed 44 hypothermic ED patients: 25 patients in the extracorporeal rewarming group (median temperature 24.1°C, 84% with cardiac arrest) and 19 patients in the conventional rewarming group (median temperature 26.3°C, 37% with cardiac arrest; 89% received an intravascular rewarming catheter). The median rewarming rate was greater in the extracorporeal versus conventional group (2.3°C/h vs. 1.5°C/h, absolute difference 0.8°C/h, 95% confidence interval [CI] 0.3–1.2°C/h) yet hospital survival was similar (68% vs. 74%). Among patients with cardiac arrest, hospital survival was greater in the extracorporeal versus conventional group (71% vs. 29%, absolute difference 42%, 95% CI 4%–82%). Conclusions: Among ED patients with severe hypothermia and cardiac arrest, survival was significantly higher with ECMO versus conventional rewarming. Among all hypothermic patients, ECMO use was associated with faster rewarming than conventional methods.